The image of Olexander Dovzhenko in the journalism of the Ukrainian diaspora (on the material of literary and critical portraits by Yu. Lavrinenko and I. Koshelivets) (Literatures of the World: Poetics, Mentality and Spirituality, 2014)
Lawrynenko’s work "Olexander Dovzhenko" and Koshelivets’s "On a dark place in the biography of Olexander Dovzhenko" devoted to figures filmmaker, writer Olexander Dovzhenko. They criticized pursued several goals – debunking the myth of Soviet O. Dovzhenko as Soviet (Russian) artist, playing his "alive image" with all the contradictions, abuse problems of Ukrainian society and forming the image of Ukraine. Therefore, the study of these literary criticism portraits seems important, especially for understanding the integrity of the Ukrainian literary critical process twentieth century. Secondly, they are topical and current problems in Ukrainian society. Thirdly, in theoretical terms, they realized imaginative communication model, which is one of the most important phenomena of modern society.Disclosure biography O. Dovzhenko occurred in parallel with the fate of the Ukrainian people. In the image specificity in publicism – express ideas through concrete images to form public opinion. This is accomplished in science publicism of Yu. Lawrynenko and I. Koshelivets at different levels of meaningful text – personal, artistic, psychological and ideological, which violated the relevant issues – person and life, person and work, person and governance, person and a homeland. They resolved through the image O. Dovzhenko and translate into ideological conclusion – despite various forms of oppression not obey the spirit, and live for our native land. Unlike Soviet critics, Diaspora’s publicists served the image O. Dovzhenko as undefeated patriot, martyr and fighter for Ukrainian values which he suffered. Thus the image of O. Dovzhenko acquires symbolic value as the embodiment of an oppressed Ukrainian nation, but unconquered spirit. Sought in a way to inspire confidence in the reader, public opinion about Ukraine as an equal republic with Russia that time the Soviet Union, which has its own national, cultural, language identity, reflecting public opinion Ukrainian emigration.
Keywords: the image of O. Dovzhenko; scientific publicism; literary criticism portrait; problems of Ukrainian society; Ukrainian Diaspora